Soft loans as an instrument of development finance: A comparative assessment and options for the future - Livia Fritz; Werner Raza (Austrian Foundation for Development Research (ÖFSE), 2014)
Within the framework of the Post-2015 Development Agenda, discussions on Financing for Development and the future of Official Development Assistance (ODA) have intensified. Amongst the instruments under review are soft loans. Though originally conceived as export promotion tools, development objectives have recently become more prominent in soft loan policies. Albeit regulated through the Arrangement on Officially Supported Export Credits, soft loans claim a place amongst the instruments of development policy. By means of comparative case study analysis, this paper examines the relevance of soft loans as an instrument of development policy. We discuss three characteristics of soft loan financing: (i) the institutional heterogeneity of programmes between countries, (ii) the hybrid nature of the instruments between export promotion and development objectives, and (iii) the underlying notions of development. Upon that basis, scenarios for the future use of soft loans as an instrument of development finance are presented.
Keywords: 330; soft loans; post-2015 development agenda; development finance; (un)tying; export promotion